8-Chloro-Adenosine Inhibits Proliferation of MDA-MB-231 and SK-BR-3 Breast Cancer Cells by Regulating ADAR1/p53 Signaling Pathway. (9th September 2020) - Ding, Hong-Yue; Yang, Wan-Yong; Zhang, Li-Hong; Li, Li; Xie, Feng; Li, Hua-Yi; Chen, Xiao-Yu; Tu, Zeng; Li, Yi; Chen, Yong; Yang, Sheng-Yong
8-Chloro-adenosine (8-Cl-Ado) has been shown to exhibit its antitumor activity by inducing apoptosis in human lung cancer A549 and H1299 cells or autophagy in chronic lymphocytic leukemia, and MDA-MB-231 and MCF-7 breast cancer cells. Adenosine deaminases acting on RNA 1 (ADAR1) is tightly associated with cancer development and progression. The aim of this study was to investigate the role of ADAR1 in the proliferation of MDA-MB-231 and SK-BR-3 breast cancer cell lines after 8-Cl-Ado exposure and its possible mechanisms. After 8-Cl-Ado exposure, CCK-8 assay was performed to determine the cell proliferation; flow cytometry was used to analyze the cell cycle profiles and apoptosis; and the protein levels of ADAR1, p53, p21, and cyclin D1 were measured by western blotting. The results showed that the cell proliferation was greatly inhibited, G1 cell cycle was arrested, and apoptosis was induced after 8-Cl-Ado exposure. ADAR1 and cyclin D1 protein levels were dramatically decreased, while p53 and p21 levels were increased after 8-Cl-Ado exposure. Moreover, the cell growth inhibition was rescued, apoptosis was reduced, and p53 and p21 protein levels were downregulated, while cyclin D1 was upregulated when cells were transfected with plasmids expressing ADAR1 proteins. More importantly, RNA-binding domain of ADAR1 is critical to the cell growth inhibition of breast cancer cells exposed to 8-Cl-Ado. Together, 8-Cl-Ado inhibits the cell proliferation, induces G1 phase arrest and apoptosis at least by targeting ADAR1/p53/p21 signaling pathway. The findings may provide us with insights into the role of ADAR1 in breast cancer progression and help us better understand the effects of 8-Cl-Ado in the treatment of breast cancer.